ISLAM INDONESIA, ISLAM NUSANTARA DAN ISLAM BERKEMAJUAN (Perspektif Islam Indonesia yang Bhinneka) - Ahmad Hafidz Lubis (Universitas Islam Lamongan, 2018)
Abstract: Islam under Prophet Muhammad SAW is a universal religion that is humanistic, dynamic and contextual. But in reality Islam is carried out by several groups as a radical religion. This paper will examine the face of humanistic, dynamic and contextual Islam with the face of Indonesian Islam, so-called Islam Nusantara, the development of Islam, and Anti-Radicalism Islam. The results obtained are firstly, Indonesian Islam is Islam that is creatively packaged and combined with local traditions. Secondly, Islam Nusantara is a typical Indonesian Islam that upholds tolerance, mutual respect, and preserves cultures having existed since ancient times. Thirdly, Islamic thinkers in Indonesia always want to fight for their voices in offering secularism, liberalism and pluralism for the creation of progressive Islam. Fourthly, Islam Nusantara is anti radicalism Islam.Keywords: Indonesian Islam, Islam Nusantara, and Islamic Progress.